2008
DOI: 10.2214/ajr.08.1048
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Bifurcation of the Biceps Brachii Muscle and Tendon: Anatomic Considerations and Clinical Implications

Abstract: A bifurcated distal biceps brachii tendon is an anatomic variant that arises from persistent division between the short head and long head of the distal biceps brachii tendon and can be characterized with MRI. Knowledge of a bifurcated distal biceps brachii tendon is important to characterize injury to the components and to avoid pitfalls in imaging diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 7 publications
4
69
0
2
Order By: Relevance
“…They also reported in one out of 17 cases, fibres of only the short head of the biceps brachii tendon contributing to the aponeurosis. Further, they have stated that the short and long head offer varying contribution not only to the distal tendon of biceps brachii but also to the BA [6]. Athwal et al [1] reported that the BA originated from the distal part of short head of the biceps in all 15 specimens studied; whereas, Eames et al [7] stated major role of long head in the formation of BA.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…They also reported in one out of 17 cases, fibres of only the short head of the biceps brachii tendon contributing to the aponeurosis. Further, they have stated that the short and long head offer varying contribution not only to the distal tendon of biceps brachii but also to the BA [6]. Athwal et al [1] reported that the BA originated from the distal part of short head of the biceps in all 15 specimens studied; whereas, Eames et al [7] stated major role of long head in the formation of BA.…”
Section: Discussionmentioning
confidence: 96%
“…Athwal et al [1] reported that the BA originates from the short head of the biceps but have not mentioned any contribution from the long head in the formation of BA. Dirim et al [6] have reported that the BA was formed by superficial tendinous fibres arising from both short and long head. They also reported in one out of 17 cases, fibres of only the short head of the biceps brachii tendon contributing to the aponeurosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations